A system dynamics model to analyse economic challenges of apparel industry: the case study of Iran. (7th June 2021) - Sohi, Zahra Asadollahi; Shakouri, G. Hamed; Raghfar, Hossein
The apparel industry is considered a growth engine for developing countries. However, there are failure cases too. For example, Iranian producers face losing their domestic market share. To evaluate the reasons, system dynamics applied to model this industry from an economic perspective. The model is the first quantitative system dynamics model for this industry, which investigates the effect of economic variables on apparel production and import. The model can settle controversial issues between policymakers and manufacturers toward the effect of many variables such as tariff barriers, exchange rate, structural changes, wage, and inflation rates. The results show, linking up with global leaders is an effective strategy to ameliorate domestic production. However, this strategy cannot compensate for the negative effects of high inflation rates. Besides, the tariff rate and exchange rate cannot be considered as long-time industry improvement strategies since they do not remove the deteriorating effects of economic instability and high inflation rates.